2011
DOI: 10.4103/0259-1162.84197
|View full text |Cite
|
Sign up to set email alerts
|

Preanesthetic sedation of preschool children: Comparison of intranasal midazolam versus oral promethazine

Abstract: Background:Ensuring adequate preoperative sedation and anxiolysis is essential, especially in pediatric surgery. Various drugs and routes of administration have been evaluated to determine the optimal method of sedation.Materials and Methods:We selected hundred preschool children undergoing elective surgery and sedated them with either intranasal midazolam or oral promethazine syrup in the preoperative period. They were assessed with respect to their levels of sedation till the period of mask placement for ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
8
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 22 publications
(20 reference statements)
3
8
0
Order By: Relevance
“…Patients of the first group received oral midazolam syrup 0.5 mg/kg, 50 minutes before LP (9) and in the second group, patients received oral promethazine syrup 1 mg/kg, 90 minutes before the procedure (5). …”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Patients of the first group received oral midazolam syrup 0.5 mg/kg, 50 minutes before LP (9) and in the second group, patients received oral promethazine syrup 1 mg/kg, 90 minutes before the procedure (5). …”
Section: Methodsmentioning
confidence: 99%
“…Gutstein et al’s five-point sedation scale (1992) was used in both groups to evaluate the children’s sedation levels (5,13), 30, 25, 20, 15, 10 and 5 minutes before the LP.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…12 In this case, either intranasal midazolam 0.3mg/kg, 30 minute prior to induction of general anesthesia or oral promethazine surup 1mg/kg, 90 minute prior to induction of general anesthesia was given to chosen children undergoing elective surgery. The study concluded that either midazolam or promethazine may be used as premedication as both of them are efficacious drugs.…”
mentioning
confidence: 99%